Metagenomic Insights into Pigeon Gut Microbiota Characteristics and Antibiotic-Resistant Genes - Wei Dai; Haicong Zhu; Junhong Chen; Hui Chen; Dingzhen Dai; Jian Wu (Biology)
Background: Antibiotics were extensively used in the pigeon breeding industry previously to promote growth and prevent disease, leading to the spread of antibiotic-resistant genes (ARGs) in gut microbes, which has become a major public health concern. Methods: A metagenomic analysis was performed to investigate the gut microbial communities and ARGs in young and older pigeons in Nanjing, Jiangsu Province, China. Results: There were obviously distinct gut microbiota and functional compositions between young and older pigeons. Both Pseudomonadota and Uroviricota were dominant in young and older pigeons. Although sharing 24 gut microbiota phyla between young and older pigeons, Bacillota and Pseudomonadota were the dominant microbial phyla in them, respectively. Besides the shared metabolic pathways and biosynthesis of secondary metabolites, biosynthesis of amino acids was the most abundant Kyoto Encyclopedia of Genes and Genomes (KEGG) function in young pigeons, while microbial metabolism in diverse environments was abundant in older pigeons. A total of 142 ARGs conferring multidrug resistance, tetracycline, and aminoglycoside resistance were identified; the most abundant gene in young pigeons was tetracycline-tetW, while in older pigeons, it was multidrug-acrB. Conclusions: Our findings revealed significant differences in the gut microbial communities and ARGs between young and older pigeons. This study enhances our understanding of pigeon gut microbiota and antibiotic resistomes, contributing to knowledge-based sustainable pigeon meat production.